Comparison on seed germination and seedling growth between Indonesian local corn cultivars for decide the quality of seed (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Wawo AH, Sumbogo VG, Lestari P. 2020. Comparison on seed germination and seedling growth between Indonesian local corn cultivars for decide the quality of seed. Biodiversitas 21: 3189-3199. Each region in Indonesia has local corn cultivars (Zea mays L), for example, South Sulawesi has some Pulut Pangkajene cultivars and Purbalingga, Central Java has Entog and Senggani cultivars. Compared to hybrid corn, local corn has its advantages such as dry resistance, short life, and specific taste. The identification of seed germination and seedling growth for Pangkajene corn (South Sulawesi), Entog and Senggani corns (Purbalingga) has not been performed, thus, specific characteristics to differ those three corn cultivars have not been available. The study aims to establish the characteristics of local corn cultivars, comprise the seed germination, seedling growth, and determine the best local corn cultivars for supporting food sources. This research has Factorial patterned with a Completely Randomized Design and it was repeated 4 times. The main factor is the germination facility, namely germination chamber and nursery house. Meanwhile, the second factors are corn cultivars, namely Pangkajene, Entog, and Senggani. The result shows that the Pangkajene and Entog cultivars have higher germinability and germination value compared to Senggani corn cultivar. Pangkajene and Senggani cultivars have higher seedling growth than Entog cultivar seedlings characterized by high relative growth rate (R) values. The Pangkajene cultivar has higher quality compared to 2 local corn cultivars of Entog and Senggani from Purbalingga (Central Java). Further, Senggani cultivars have higher quality than Entog cultivars.
Keywords: Local corn; Pangkajene; Entog; Senggani; Germanibility